New Characterizations of k-Uniformly Extremely Convex Banach Spaces - Suyalatu Wulede (Journal of Function Spaces)
Two characterizations of k-uniformly extremely convex spaces are given in this paper. As special cases for k=1, two necessary and sufficient conditions of uniform extreme convexity are presented and a characteristic inequality of uniformly extremely convex spaces is given.